THE SPIRITUALITY OF PEDICAB DRIVERS A CASE STUDY AT TRUNOJOYO STREET BOJONEGORO CITY EAST JAVA - Yogi Prana Izza (Teosofia: Indonesian Journal of Islamic Mysticism, 2018)
This paper aims to describe the spirituality of "suburban humans" who in this case are pedicab drivers on the Trunojoyo road in Bojonegoro city. The anthropological approach is used with the focus on: the meaning and needs of spirituality for pedicab drivers, the spiritual dimension of pedicab drivers and the factors that influence their spirituality. The results of this study are expected to be input into the development and improvement of spirituality as a basic human need.